Early life adverse exposures in irritable bowel syndrome: new insights and opportunities - Guo Qiong Zhou; Meng Jie Huang; Xin Yu; Na Na Zhang; Shan Tao; Ming Zhang (Frontiers Media S.A., 2023)
Irritable bowel syndrome (IBS) is a prevalent functional gastrointestinal disorder worldwide. Extensive research has identified multiple factors contributing to its development, including genetic predisposition, chronic infection, gut dysbiosis, aberrant serotonin metabolism, and brain dysfunction. Recent studies have emphasized the critical role of the early life stage as a susceptibility window for IBS. Current evidence suggests that diet can heighten the risk of IBS in offspring by influencing the microbiota composition, intestinal epithelium structure, gene expression, and brain-gut axis. The use of antibiotics during pregnancy and the neonatal period disrupts the normal gut microbiota structure, aligning it with the characteristics observed in IBS patients. Additionally, early life stress impacts susceptibility to IBS by modulating TLR4, NK1, and the hypothalamic-pituitary-adrenal (HPA) axis while compromising the offspring's immune system. Formula feeding facilitates the colonization of pathogenic bacteria in the intestines, concurrently reducing the presence of probiotics. This disruption of the Th1 and Th2 cell balance in the immune system weakens the intestinal epithelial barrier. Furthermore, studies suggest that delivery mode influences the occurrence of IBS by altering the composition of gut microbes. This review aims to provide a comprehensive summary of the existing evidence regarding the impact of adverse early life exposures on IBS during pregnancy, intrapartum, and neonatal period. By consolidating this knowledge, the review enhances our understanding of the direct and indirect mechanisms underlying early life-related IBS and offers new insights and research directions from childhood to adulthood.